Physical and optical properties of Li2O-MgO-B2O3 doped with Sm3+ - Reduan, Siti Aisyah; Hashim, Suhairul; Ibrahim, Zuhairi; Alajerami, Yasser Saleh Mustafa; Abu Mhareb, Mohammad Hasan; Said Dawaud, Raghda Saeif Eddin; Tamchek, Nizam (Elsevier, 2014)
Samarium oxide doped lithium magnesium borate glass has been prepared using conventional melting method. The density and molar volume have been calculated and analyzed while their optical properties were studied by measuring the optical absorption and luminescence spectra at room temperature. From the XRD results, since the patterns do not exhibit any diffraction line thus it confirms their amorphous nature. It was found that the density of the glass samples increased and the molar volume decreased with respect to Sm3+ ions content. Meanwhile, the absorption spectra of this study showed four absorption bands with most outstanding peak at 1230 nm (6H5/2–6F7/2). Three emitted spectra transition were observed in this study which are 4G5/2–6H5/2 (blue), 4G5/2–6H9/2 (green), and 4G5/2–6H11/2(yellowish green). A great enhancement in the PL peaks at green region are observed particularly with the 0.5 mol% concentration, which may attribute to the energy transfer from Mg2+ to the trivalent ions of samarium oxide. Beyond the optimum concentration an opposite effect was remarked. This dwindling is attributed to the concentration quenching phenomenon. The current results agreed with other systematic studies that Sm3+ doped with lithium magnesium borate glasses are attractive solid-state laser materials for generation of various visible lights.